Added predictive value of childhood physical fitness to traditional risk factors for adult cardiovascular disease - Fraser, Brooklyn J; Blizzard, Leigh; Tomkinson, Grant R; Dwyer, Terence; Venn, Alison J; Magnussen, Costan G (Oxford University Press (OUP), 2025)
Aims
Childhood physical fitness is a predictor of cardiovascular (CV) health but is underutilized in health surveillance. This study determined the predictive utility of child physical fitness levels on obesity, hypertension, dyslipidaemia, and the metabolic syndrome (MetS) in adulthood over traditional CV risk factors in childhood.
Methods and results
This is a longitudinal cohort study of Childhood Determinants of Adult Health Study participants who had their fitness [cardiorespiratory fitness (CRF): 1.6 km run/walk, physical work capacity at 170 b.p.m.; muscular fitness: dominant handgrip strength and standing long jump] measured as children and their CV health assessed as children and adults (mean follow-up = 27 years). Participants had their body mass index (BMI), waist circumference, blood pressure, fasting blood sample (lipids, glucose), and smoking status assessed as children in 1985 and in early adulthood (2004–06, 26–36 years) and/or middle adulthood (2014–19, 36–49 years) where obesity, hypertension, dyslipidaemia, and MetS were defined. Logistic regression was used to model associations (n range = 578–5049). Additionally considering childhood CRF or muscular fitness improved the ability to discriminate and fit models to predict adult obesity, low HDL cholesterol (HDL-C), and MetS when added to demographics (age and sex) and the corresponding measure in childhood (BMI, HDL-C, and CV risk score), as reflected by increments in area under the curve (Δrange = 0.003–0.022), net reclassification index (range = 0.026–0.149), integrated discrimination index (range = 0.003–0.027), reductions in deviance and Brier scores, and statistically significant likelihood ratio tests.
Conclusion
Cardiorespiratory fitness and muscular fitness are independent health indicators that could complement other risk factors in childhood to identify individuals at increased long-term CV risk.